2022
DOI: 10.21037/atm-22-604
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 protects against cerebral ischemia-reperfusion injury by suppressing programmed necrosis and inflammatory signaling pathways

Abstract: Background: The NOD-like receptor family pyrin domain-containing 3 (NLRP3) -mediated neuroinflammation is linked to neuronal necroptosis in cerebral ischemia-reperfusion (I/R) injury, especially in cerebral ischemic penumbra. This study was designed to investigate the regulation of nuclear factor E2related factor-2 (Nrf2) on NLRP3 inflammasome in necroptosis signal pathway induced by I/R injury. Methods:We investigated the mechanisms of Nrf2-negative regulation in necroptosis signaling pathway by using middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Bai et al demonstrated that the EV71 virus led to apoptosis through excessive ROS via Nrf2 in Vero and RD cells . Chen et al also proved that Nrf2 regulated NQO1 to reduce ROS, which inhibited the NLRP3 inflammasome and necroptosis in cerebral ischemia–reperfusion injury . Our results proved that inhibition of Nrf2 increased 1,3-DCP-mediated ROS, which led to necroptosis in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 70%
“…Bai et al demonstrated that the EV71 virus led to apoptosis through excessive ROS via Nrf2 in Vero and RD cells . Chen et al also proved that Nrf2 regulated NQO1 to reduce ROS, which inhibited the NLRP3 inflammasome and necroptosis in cerebral ischemia–reperfusion injury . Our results proved that inhibition of Nrf2 increased 1,3-DCP-mediated ROS, which led to necroptosis in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 70%
“…According to KEGG pathway enrichment, NRDEGs were primarily related to necroptosis ( Gong et al, 2019 ), NF−kappa B and NOD−like receptor pathways, which were all the immune inflammatory response pathways ( Arbibe et al, 2000 ; Caruso et al, 2014 ). Research has suggested that nuclear factor E2-related factor-2 (Nrf2) shows negative regulation on NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome during necroptosis ( Chen et al, 2022 ). Notably, the analysis results demonstrated the enrichment of necroptosis pathway in functional annotation, suggesting the role of necroptosis in AMI pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG analyses indicated that NRGs are mainly enriched in the shigellosis and NOD-like receptor signaling pathways in addition to necroptosis. Interestingly, the NOD-like receptor was found to be linked to neuronal necroptosis in cerebral ischemia-reperfusion injury [ 31 ]. Blériot, C. et al .…”
Section: Discussionmentioning
confidence: 99%